1974
DOI: 10.1029/jc079i015p02161
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the responses of the general circulation at 700 mbar to solar geomagnetic disturbance

Abstract: The northern hemisphere 700-mbar contour heights from 20 ø to 70øN for the period 1947-1970 are studied in conjunction with 272 key days, where the daily increase of the Ci index equals or exceeds 1.0. The superposed epoch method is applied from 33 days before to 66 days after the key day for a variety of zonal and meridional indices. It is shown that the 700-mbar height difference between 20 ø and 55øN increases significantly in winter 4 days following geomagnetic disturbance (in summer a less prominent but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…The decrease is greatest between 70 and 1103 west longitude and between 40 and 703 north latitude and corresponds to an increase by as much as 7% in tropospheric westerly #ow, which translates to an increase in mean zonal wind velocity of about 0.6 m/s. The Northern Great Plains lie near the center of the region where the strongest response by zonal winds has been reported (Stolov and Shapiro, 1974; see discussions by Anderson, 1992Anderson, , 1993. Statistical analyses by Tinsley and Deen (1991) of 33 yr of meteorological data show a clear correlation between the intensity of cyclonic circulation in mid-latitude oceanic regions with changes in cosmic-ray #ux following geomagnetic storms.…”
Section: Aridity Cycles In Last 2000 Yrmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease is greatest between 70 and 1103 west longitude and between 40 and 703 north latitude and corresponds to an increase by as much as 7% in tropospheric westerly #ow, which translates to an increase in mean zonal wind velocity of about 0.6 m/s. The Northern Great Plains lie near the center of the region where the strongest response by zonal winds has been reported (Stolov and Shapiro, 1974; see discussions by Anderson, 1992Anderson, , 1993. Statistical analyses by Tinsley and Deen (1991) of 33 yr of meteorological data show a clear correlation between the intensity of cyclonic circulation in mid-latitude oceanic regions with changes in cosmic-ray #ux following geomagnetic storms.…”
Section: Aridity Cycles In Last 2000 Yrmentioning
confidence: 99%
“…It is not known, however, how these upper-atmosphere winds affect the lower atmosphere (troposphere). Roberts and Olson (1973) observed that strong solar}geomagnetic disturbances in the troposphere during winter were often followed within a few days by a deepening of subpolar low-pressure systems (300 mbar troughs) over the North Paci"c. Stolov and Shapiro (1974) studied the 700 mbar heights in the northern hemisphere between 20 and 703 N for 33 d before and 66 d following 272 solar}geomagnetic disturbances over the period from 1947 to 1970. They noted that the most signi"cant response to these disturbances was a decrease in the 700 mbar height in winter relative to the average for the same period (`climatologya) four days following a disturbance.…”
Section: Aridity Cycles In Last 2000 Yrmentioning
confidence: 99%
“…The heaviest rainfalls are mostly associated with the increase in easterlies on or around the dates of singularities noticed. Shapiro and Stolov [26] have found significant increases in westerly winds at the 700 mb level in the longitude belt from 90°W to 180°W three to four days after the magnetic storms. Comparing geomagnetic data with the data on tropospheric and stratospheric circulation character-140 R.S.…”
Section: Discussionmentioning
confidence: 97%
“…days later by an increase in tropospheric zonal winds at 700 mbar, and by the fact that Elk Lake lies near the center of the region between the Great Lakes and Hudson Bay where the strongest response to zonal winds has been reported (Stolov and Shapiro, 1974; see discussion by Anderson, Chapter 5). Another interesting aspect of the association is that the strongest oscillations in both varve thickness (regional surface winds) and radiocarbon (solar activity) occur at the time scale of the Maunder deviations, during which there appears to be a maximum effect on the solar wind (E. J.…”
Section: Possible Solar Origin Of Fine-scale Mid-holocene Climatic Osmentioning
confidence: 96%